CorpoBrasilities in the Circus Ring:: Afro-Brazilian toys in the creative and pedagogical processes of the circus artist - Santos, Lau (Revista Brasileira de Estudos da Presença, 2025)
This article discusses how Afro-Brazilian cultural ancestry should be a fundamental creative pedagogical assumption in the training of Brazilian circus artists in contemporary times, in an anti-colonial aesthetic-political positioning. It starts with two questions: How to use Afro-Brazilian techniques such as capoeira in the training of the artist and his/her circus acts in contemporary times? What can be understood as a pedagogical and creative decolonization of Brazilian circus art, respecting its ancient tradition? The risk, the playfulness and the appreciation of cultural reality are common points that strategically enhance Brazilianness and its corporeality, as well as circus arts.